The formation of civil society in Ukraine under present conditions - Пильгун, Наталія Василівна; Повєткін, Дмитро Олегович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The problem of relationship of civil society with the state within its theoretical, social and political aspects was analyzed. The attention was paid to the institutional pre-conditions of both civil and political societies differentiation as well as to the features of democratic governance in the terms of social and state transformation. The interest of researchers on the theme of civil society is not fading since the appearance of this phenomenon. Likewise the rule of law, according to most jurists, the civil society is the most suitable environment for the implementation of the rights and freedoms of the individual and citizen, the ideals of freedom and equality and other democratic and humanistic principles. Formation of civil society is complicated and multifaceted process, however its essential and irreplaceable participant has always been and shall be the individual, who in any case has a sense of justice and is able to interpret and evaluate the legal reality, which surrounds, make decisions and take actions that have a legal consequences. The path to the civil society and the Rule of Law goes only through democratization of legal awareness of citizens and try to avoid this step is impossible. The fact is that the source of civil society in the country should be the people and the so called civil society institutes, imposed "from above" really are not. However, the state's influence can still be useful. Raising the level of sense of justice of the population through the real spread of legal information, provision of effective legal training and quality education can become as a much important step towards establishing a legal state and civil society as political and economic transformation in Ukraine.